Bacteria in the ECHAM5-HAM global climate model - A. Sesartic; U. Lohmann; T. Storelvmo (Atmospheric Chemistry and Physics, 2012)
Some bacteria are among the most active ice nuclei found in nature due to the ice nucleation active proteins on their surface, which serve as active sites for ice nucleation. Their potential impact on clouds and precipitation is not well known and needs to be investigated. Bacteria as a new aerosol species were introduced into the global climate model (GCM) ECHAM5-HAM. The inclusion of bacteria acting as ice nuclei in a GCM leads to only minor changes in cloud formation and precipitation on a global level, however, changes in the liquid water path and ice water path are simulated, specifically in the boreal regions where tundra and forests act as sources of bacteria. Although bacteria contribute to heterogeneous freezing, their impact is reduced by their low numbers compared to other heterogeneous IN. This result confirms the outcome of several previous studies.